Hemorrhagic cutaneous necrosis in the course of treatment with coumarin derivative - Olivera, Daniel E.; Mesa, Guillermo; Silvera, Daniel; Praderi, Jorge (Cirugía del Uruguay, 1978)
A patient with bilateral venous thrombosis of lower limbs presented cutaneous thrombosis during treatment with cumarine derivates. Diagnosis of necrotizing cutaneous angeitis is established on the basis of humoral signs of inmunological hyperactivity and hystopathological findings. The convenience of an inicially conservative attitude with respect to cutaneous lesions is stressed in this paper.